Enlarged Perivascular Spaces Are Negatively Associated With Montreal Cognitive Assessment Scores in Older Adults - Libecap, Timothy J.; Zachariou, Valentinos; Bauer, Christopher E.; Wilcock, Donna M.; Jicha, Gregory A.; Raslau, Flavius D.; Gold, Brian T. (Frontiers in Neurology, 2022)
Emerging evidence suggests that enlarged perivascular spaces (ePVS) may be a clinically significant neuroimaging marker of global cognitive function related to cerebral small vessel disease (cSVD). We tested this possibility by assessing the relationship between ePVS and both a standardized measure of global cognitive function, the Montreal Cognitive Assessment (MoCA), and an established marker of cSVD, white matter hyperintensity volume (WMH) volume. One hundred and eleven community-dwelling older adults (56-86) underwent neuroimaging and MoCA testing. Quantification of region-specific ePVS burden was performed using a previously validated visual rating method and WMH volumes were computed using the standard ADNI pipeline. Separate linear regression models were run with ePVS as a predictor of MoCA scores and whole brain WMH volume. Results indicated a negative association between MoCA scores and both total ePVS counts (p = <0.001) and centrum semiovale ePVS counts (p = < 0.001) counts. Further, WMH volumes were positively associated with total ePVS (p = 0.010), basal ganglia ePVS (p = <0.001), and centrum semiovale ePVS (p = 0.027). Our results suggest that ePVS burden, particularly in the centrum semiovale, may be a clinically significant neuroimaging marker of global cognitive dysfunction related to cSVD.